West-facing view of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
The west-facing view of the Suswani Mata Temple reveals a structure surrounded by a large courtyard. At the centre stands the old temple structure, painted in white, red, and golden colours. There are a few sculptural fragments to the south side of the temple. A kera tree believed to be auspicious by the devotees of Suswani Mata is situated to the south of the temple.